usuń niewymiernosc z mianownika

Usuń Niewymiernosc Z Mianownika class=

Odpowiedź :

Odpowiedź:

A)

[tex] \frac{2 \sqrt{3} }{2 + \sqrt{5} } = \frac{2 \sqrt{3} \times (2 - \sqrt{5} )}{2 + \sqrt{5} \times (2 - \sqrt{5}) } = \frac{4 \sqrt{3} - 2 \sqrt{15} }{4 - 5} = \frac{4 \sqrt{3} - 2 \sqrt{15} }{ - 1} = - 4 \sqrt{3} + 2 \sqrt{15} [/tex]

B)

[tex] \frac{3 \sqrt{2} + 3}{3 - 3 \sqrt{2} } = \frac{3 \sqrt{2} + 3 \times (3 + 3 \sqrt{2)} }{3 - 3 \sqrt{2} \times (3 + 3 \sqrt{2)} } = \frac{9 \times 2 + 2 \times 3 \times 3 \sqrt{2 } + 3 \times 3}{9 - 9 \times 2} = \frac{18 + 18 \sqrt{2} + 9 }{ - 9} = \frac{27 + 18 \sqrt{2} }{ - 9} = - 3 - 2 \sqrt{2} [/tex]

Mam nadzieję, że dobrze :)